Emergence of multiple clade 2.3.2.1 influenza A (H5N1) virus subgroups in Vietnam and detection of novel reassortants. - Creanga, A; Thi Nguyen, D; Gerloff, N; Thi, H; Balish, A; Dang Nguyen, H; Jang, Y; Thi Dam, V; Thor, S; Jones, J; Simpson, N; Shu, B; et al. (2013)
Phylogenetic analyses of 169 influenza A(H5N1) virus genomes were conducted for samples collected through active surveillance and outbreak responses in Vietnam between September 2010 and September 2012. While clade 1.1 viruses persisted in southern regions, three genetically distinct subgroups of clade 2.3.2.1 were found in northern and central Vietnam. The identification of each subgroup corresponded with detection of novel reassortants, likely due to their overlapping circulation throughout the country. While the previously identified clade 1.1 and A/Hubei/1/2010-like 2.3.2.1 genotypes remained the predominant viruses detected, four viruses were found to be reassortants between A/Hubei/1/2010-like (HA, NA, PB2, PB1, PA, NP) and A/duck/Vietnam/NCVD-885/2010-like (M, NS) viruses and one virus was identified as having A/duck/Vietnam/NCVD-885/2010-like HA, NA, PB1, and NP with A/Hubei/1/2010-like PB2 and PA genes. Additionally, clade 2.3.2.1 A/Hong Kong/6841/2010-like viruses, first detected in mid-2012, were identified as reassortants comprised of A/Hubei/1/2010-like PB2 and PA and A/duck/Vietnam/NCVD-885/2010-like PB1, NP, NA, M, NS genes.